Die Wanderung der Yoruba nach Ghana und ihre Rückkehr nach Nigeria - Hundsalz, Mathias (ERDKUNDE, 1972)
Under the provisions of an Act promulgated on 18. 11. 1969, all foreigners in Ghana without a passport and evidence of a regular income must leave the country immediately. Among others affected by this were almost 100,000 Yoruba from West Nigeria most of whom had already migrated to Ghana during the British colonial phase. The Yoruba have never integrated themselves into Ghanaian society. Their relationship to each other and their social linkages with relatives who stayed behind in their home areas were still, after decades of living in Ghana, stronger than their adherence to the Ghanaians. The most important area of out-migration in West Nigeria was the heavily populated transition area from rain forest to savanna, including the former Oyo Empire stretching to the north. The most favoured migration destinations in Ghana were the urban centres of the south, (especially Accra, Kumasi, Sekondi-Takoradi) and the north (especially Tamale), as well as the mining areas and the cocoa belt in the south. Pronounced efforts to retain their physical and social environment can be identified in the patterns of out-migration. The flight from Ghana back to Nigeria had, as its first effect, an often heavy increase in population in the affected home areas. The problems which resulted from this are, however, already being overcome by a renewed out-migration to attractive areas within Nigeria and through the efforts of the refugees themselves to transform the still widespread subsistence agriculture into market-oriented cultivation of cash crops.